بناء الأسلوب في الشعر السوري الحديث: شعر التفعيلة أنموذجا - عبشي، نزار محمد (جامعة البعث, 2017)
الدراسة المؤلمة تري أن الولوج إلى بناء الأسلوب في شعر التفعيلة في الشعر السوري الحديث يمكن أن يكون من خلال المظاهر والصور الخصبة فيه، ولكن هذه المظاهر والصور والتجليات اللغوية والفنية لا بد أن تنفتح على بقية البني المتحققة المتفاعلة معها من ناحية، وربما جاوزتها نحو آفاقها المضمونة البعيدة من الناحية أخري. ونأمل من خلال هذه القراءة التحليلية-المنطلقة من النص والتي تستنطق الكامن نأمل أن تظهر شيئا ما على المستويين المنهجي، والتحليلي الفني؛ مما يشكل إضافة حداثية مؤثرة، وهذا ما نطمح إلية من خلال هذا البحث، ونجزم أن غائية الدراسة هنا لا تقف عند ذكر البني الأسلوبية في شعر التفعيلة في الشعر السوري، بل ونأمل أن تسبر هذه الدراسة اللغة النصية لتنفيذ إلى مقولاتها الفكرية بروح نقدية حداثية، ويتأسس ذلك على مقاربة علمية موضوعية قدر الإمكان.
The proposed study suggests that exploring style structure in the Taf'eela Verse (free verse) of modern Syrian poetry may be achieved through the manifestations and rich pictures that it encompass. But these manifestations, pictures, and linguistic and artistic revelations must usher the way to the rest of the materialized structures which are interacting with it, on the one hand, and perhaps it overpasses them towards their distant implied spheres, on the other hand. We hope through this analytical reading –starting from the text and uncovering what is concealed— to show point out to something on two levels –methodological and artistic/analytical. This would actually shape an effective modern addition. In fact, this is what we hope to achieve in this research. We categorically assert that the purpose of this study is not confined to mentioning the stylistic structures in taf'eela verse in Syrian poetry, but we also hope that this study will probe the textual language to break through to its intellectual expressive categories in a modern critical spirit; and this is founded on an objective scientific comparison as much as possible.
Keywords: الشعر العربي -- الشعر الحر -- شعر التفعيلة -- الأساليب الشعرية -- سوريا